Continuous theta-burst stimulation over the left posterior inferior frontal gyrus induced compensatory plasticity in the language network - An, HyunJung; Bashir, Shahid; Cha, Eunsil; Lee, Jeongeun; Ohn, Suk Hoon; Jung, Kwang-Ik; Yoo, Woo-Kyoung (Frontiers in Neurology, 2022)
Abstract Introduction Continuous theta-burst stimulation (cTBS) has been used as an effective tool in inducing inhibitory aftereffect within a short time periods in the motor cortex; this has been demonstrated in the language network to a limited degree with controversial effect. In this study, we aimed to delineate the offline effect of cTBS-induced changes to the left posterior inferior frontal gyrus (pIFG) in healthy subjects using fMRI. Methods Twenty healthy, normal subjects (mean age: 30.84 years) were recruited. They all were right-handed and had no contra-indications for fMRI or cTBS. They were randomly assigned into the treatment group or the sham control group. Results ANOVA showed that cTBS had a significant main effect only when the sham treatment was subtracted from the real stimulation in left superior temporal, left inferior frontal gyrus, thalamus, and right insular cortex (uncorrected p < 0.002). The subjects’ post-cTBS condition differed significantly from their pre-cTBS condition in the left pIFG (uncorrected p < 0.002). There were interactions in the pIFG, bilateral superior parietal lobules, left superior temporal, left supramarginal, and left cuneus areas. The application of cTBS induced increased BOLD signals in language-related networks by stimulating the left pIFG (BA 44). This implies that inhibiting the pIFG led to increased use of language network resources. Conclusion This study demonstrated cTBS-induced changes in the language network caused by stimulation of the left pIFG. Based on these findings, future studies on the therapeutic effects of cTBS on the right Broca’s homologue area are warranted.